PECULIARITIES OF AN INDIVIDUAL APPROACH TO HIGH SCHOOL STUDENTS MAJORING IN TECHNOLOGY - Andriy Uruskyi (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The features of the methodology of the implementation of an individual approach to high school students majoring in technology are analysed. The main stages of the implementation have been defined as the analysis of the individual student characteristics; grouping 10-11 grade students; usage of the modern informational and communicational techniques and a set of facilities of differentiated studying. The examples of the differentiated tasks for different phases of the high school training such as providing training material by teachers; academic progress monitoring; self-studying materials; fulfilling tasks of practical (laboratory and practical) works; goods manufacturing; carrying out creative projects have been provided.